Strategi Pemasaran Politik Partai Golkar Dalam Pemenangan Pasangan Rahmad Pada Pilkada Bondowoso 2024 - Muhammad Rizal Bintang Firmansyah; Suwignyo Widagdo; Tamriatin Hidayah (GLOBAL SCIENTS PUBLISHER, 2026)
The purpose of this study is to analyze the political marketing strategy of the Golkar Party in winning the candidate pair Ra Hamid and Ra As'ad (RAHMAD) in the 2024 Bondowoso Pilkada. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The results showed that the Golkar Party successfully implemented an integrated strategy of push, pull, and pass marketing. Key success factors include the repositioning of the candidate's religious-intellectual image, a